Rancangan Faktorial Model Campuran Menggunakan Metode Maksimum Likelihood - Andi Tenri Riski Amalia; Raupong Raupong; Andi Kresna Jaya (ESTIMASI: Journal of Statistics and Its Application, 2022)
Variance is the amount of statistics which measures how far a set of numbers in observation are spread out from its mean. In experimental design, variance are caused by the effect of treatment, block and error of experimental can be estimated by variability of error that commonly referred to variance component. In this study, the maximum likelihood method with Hartley Rou modification was used followed by the Newton Raphson method which was applied to a complete randomized block factorial design mixed model with factor A being fixed and factor B being random. The results of this study for rice production data showed that there is a significant effect on the interaction of genotype and location on rice production. The estimated value of the variance component obtained indicates that there are variations in the influence of location factors, and genotype and location interaction factors on rice production.